2006
DOI: 10.1111/j.1365-2796.2006.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B as a long‐term predictor of mortality in type 1 diabetes mellitus: a 15‐year follow up

Abstract: Abstract. Stettler C, Suter Y, Allemann S, Zwahlen M, Christ ER, Diem P (University of Bern, Bern, Switzerland). Apolipoprotein B as a long-term predictor of mortality in type 1 diabetes mellitus: a 15-year follow up. J Intern Med 2006; 260: 272-280.Objectives. To evaluate the association of apolipoprotein B (apo B) with mortality due to all causes, to cardiac disease and to ischaemic heart disease (IHD) in subjects with type 1 diabetes mellitus. Subjects. 165 subjects with type 1 diabetes included in the Swis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
2
5
2
Order By: Relevance
“…ApoB100 binds in a 1:1 ratio each circulating pro-atherogenic moiety, (LDL, VLDL, and IDL), and therefore, mirrors the total burden of the atherogenic cholesterol in the circulation. Increased serum apoB100 concentrations are established to be strong predictors for ischemic cardiovascular events [37]. Our findings coincide with that of a recent study reporting greater elevated apoB100 in children with type 2 diabetes relative to children with type 1 diabetes [30].…”
Section: 0 Discussionsupporting
confidence: 91%
“…ApoB100 binds in a 1:1 ratio each circulating pro-atherogenic moiety, (LDL, VLDL, and IDL), and therefore, mirrors the total burden of the atherogenic cholesterol in the circulation. Increased serum apoB100 concentrations are established to be strong predictors for ischemic cardiovascular events [37]. Our findings coincide with that of a recent study reporting greater elevated apoB100 in children with type 2 diabetes relative to children with type 1 diabetes [30].…”
Section: 0 Discussionsupporting
confidence: 91%
“…18,19 ApoB levels also were strongly linked to CV risk in patients with T1D in a 15-year follow-up study in Switzerland. 20 It is unclear why we did not observe a relationship between T1D and apoB levels in our study, although it is possible that the negative consequences of diabetes on apoB may be confined to older patients.…”
Section: Discussioncontrasting
confidence: 58%
“…Various apolipoprotein abnormalities have also been described in subjects with T1D including elevated apolipoprotein C and lipoprotein a levels[19, 20]. A 15-year follow-up study from Switzerland showed apolipoprotein B levels to be a strong predictor of cardiovascular mortality in T1D subjects[21]. However, all these studies have been done in adults with T1D.…”
Section: Discussionmentioning
confidence: 99%